Response of cathodoluminescence to crystal-plastic deformation in zircon - Timms, Nicholas Eric; Reddy, Steven (Elsevier Science BV, 2009)
Geochemical and geochronological studies of zircon are commonly supplemented by cathodoluminescence (CL) imaging because it provides a means of recognizing different generations of zircon growth at high-spatial resolution. Crystal-plastic deformation of zircon can have significant effects on zircon geochemistry. Detailed analyses from electron backscatter diffraction mapping combined with panchromatic CL imaging and hyperspectral CL mapping of several crystal-plastically deformed grains from different geological settings are used to establish the relationships between crystal-plastic deformation and CL in zircon. Results show a strong spatial association between deformation microstructures and CL response that lead to modification of CL that commonly cross-cuts primary zoning. Variable contributions from two fundamental deformation-related processes result in a variety of CL characteristics: A defect control on panchromatic CL intensity, particularly at low-angle (subgrain) boundaries; and changes in spectral CL response due to deformation-related modification of CL-active REE geochemistry. A framework is provided for the recognition of deformation-related microstructures using CL and the usefulness of CL imaging in the discrimination of these microstructures is critically evaluated.